1984
DOI: 10.3168/jds.s0022-0302(84)81409-5
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Metabolism in the Rumen

Abstract: Nitrogen metabolism is reviewed with emphasis on methods for quantitating various nitrogen-transactions in the rumen of animals on a variety of diets. Ammonia kinetics, microbial cell synthesis, the inputs of endogenous nitrogen, degradation of dietary protein, and availability to the animal of dietary bypass protein are discussed. The efficiency of microbial protein from the rumen is discussed in relation to the ratio of protein to energy in the nutrients available to meet the requirements of the animal. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
150
1
14

Year Published

1988
1988
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 288 publications
(173 citation statements)
references
References 89 publications
8
150
1
14
Order By: Relevance
“…d -1 ), alone or with Met, increased plasma Lys concentration by 117 and 135% respectively compared to treatment 'Met'. Since AA absorption by the rumen wall is negligible [10], these results confirmed that a substantial proportion of the administered AA escaped the rumen and was absorbed from the small intestine. The changes in plasma AA profile 3 h after AA administration confirmed that this mechanism was rapid.…”
Section: Resultssupporting
confidence: 71%
“…d -1 ), alone or with Met, increased plasma Lys concentration by 117 and 135% respectively compared to treatment 'Met'. Since AA absorption by the rumen wall is negligible [10], these results confirmed that a substantial proportion of the administered AA escaped the rumen and was absorbed from the small intestine. The changes in plasma AA profile 3 h after AA administration confirmed that this mechanism was rapid.…”
Section: Resultssupporting
confidence: 71%
“…Unlike current recommendations for feeding dairy cattle (NRC 2001), previous protein recommendation (NRC 1989) was not specific to rumen undegradable protein (RUP) and rumen degradable protein (RDP). This is very important because proper protein nutrition in ruminants depends on consumption of RUP and RDP to support optimum rumen fermentation and microbial protein yield, provide metabolizable protein for utilization by maternal and fetal tissues (Leng and Nolan 1984) and desirable reproductive performance (Curtis et al 1985).…”
Section: Nutrient Densitymentioning
confidence: 99%
“…One of the main goals of the ruminant nutritionist is to decrease excessive protein breakdown and ammonia production by the rumen microbial population and, as a result, to increase nitrogen efficiency in the ruminant animal (Leng & Nolan, 1984). Gram-negative bacteria from the genus Prevotella (formerly classified as Bacteroides) play a significant role in the breakdown of peptides in the rumen (Bladen et al, 1961;Russell, 1983;Depardon et al, 1996).…”
Section: Introductionmentioning
confidence: 99%